From War to Peace, from Chaos to School: A Study Among Asylum-Seeking Families in Switzerland - Sanchez-Mazas, Margarita; Mottet, Geneviève; Changkakoti, Nilima (European Journal of Social Science Education and Research, 2022)
The "migrant crisis" has received a large media coverage addressing the ways to limit refugees’ settlement in European countries. Although an increasing number of asylum seekers are or will be admitted in the different states, little attention is devoted to the receiving conditions in the countries of settlement. Yet, a great amount of the incomers involve families with children, so that the schooling issue should be regarded as a major challenge for the receiving countries. Indeed, according to the largely ratified Convention on the Rights of the Child (1989), the right to education has to be implemented irrespective of the family legal status. In this paper, we will show that systematically evaluating these pupils’ resources and needs in their mother tongue should be regarded as a key for their adequate orientation into the new school system. We will report situations ranging from illiteracy to unexpected skills acquired through informal schooling or makeshift means. Moreover, on the basis of a series of interviews with the families of newly arrived pupils, we will highlight the schooling impairments these children have experienced in their home country or during their fleeing journey. We will contend that identifying these pupils’ needs and resources is a decisive tool against their undiscriminated relegation into special structures, as a result either of stereotyping or of teachers’ feeling of helplessness -which are often intertwined.